The Book of Pop Up Augmented Reality to Increase Focus and Object Recognition Capabilities for Children with Autism - Muhammad Arief Nazaruddin; Mohammad Efendi (Journal of ICSAR, 2018)
One of the extreme behavioral indicators experienced by children with autism is the difficulty of focusing through the object carefully, especially the objects that cannot attract their attention. To overcome these obstacles, medium or media that can bridge the characteristics of children with autism is needed. Books with pop up augmented reality can be a solution. The purpose of this research is to describe the feasibility of the use of books with pop up augmented reality format to improve the focus and recognition of objects for children with autism. Therefore, the design used in this research is planning design, and the respondents are students of SDLB Laboratorium of Autism UM. Based on the results of the research, the utilization of pop up augmented reality book was able to increase the autistic student appreciation on objects introduced to him. The indicator can be seen from the increased interest in design, the duration of observation, exploration of curiosity, mastery of message content, communication when observing objects or thing introduced to them.